Answers

2014-08-15T14:35:44+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
For the first leg of the journey,
V = 0 + α  t1
So  V = α  t1

for the second leg of journey of duration  t - t1 :
0 = V - β (t - t1)
0 = α t1 - β t + β t1

t1 = β t / (α + β)

V =  αt1 = α β t / (α + β )

7 4 7
thanku sir
mark it as brainliest answer and click on the Thank you link
any more questions 133